2009
DOI: 10.1111/j.1872-034x.2008.00414.x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of newly developed combination therapy of intra‐arterial 5‐fluorouracil and systemic pegylated interferon α‐2b for advanced hepatocellular carcinoma with portal venous invasion: preliminary results

Abstract: Combination therapy with intra-arterial 5-FU and systemic PEG-IFNalpha-2b may be useful as a palliative treatment for patients with advanced HCC. A prospective controlled trial using a larger population of patients with advanced HCC is needed to evaluate this new combination therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 36 publications
(55 reference statements)
0
12
0
Order By: Relevance
“…The therapeutic effects of 5‐fluorouracil combined with PEG‐IFNα‐2b may thus exceed those of 5‐fluorouracil combined with IFNα. We have already administered 5‐fluorouracil and PEG‐IFNα‐2b to patients displaying advanced HCC with PVTT and reported favorable preliminary results 15, 16. The aim of this study was to elucidate the efficacy of this therapy by analyzing the clinical results in 59 HCC patients with PVTT treated in this manner.…”
Section: Introductionmentioning
confidence: 99%
“…The therapeutic effects of 5‐fluorouracil combined with PEG‐IFNα‐2b may thus exceed those of 5‐fluorouracil combined with IFNα. We have already administered 5‐fluorouracil and PEG‐IFNα‐2b to patients displaying advanced HCC with PVTT and reported favorable preliminary results 15, 16. The aim of this study was to elucidate the efficacy of this therapy by analyzing the clinical results in 59 HCC patients with PVTT treated in this manner.…”
Section: Introductionmentioning
confidence: 99%
“…In 1999, Yano et al compared the in vivo antitumor effects of PEG-IFN-α2b and IFN-α in nude mice injected with cultured HCC cells, and found that PEG-IFN-α2b induced apoptosis more strongly than IFN-α [43]. Intra-arterial 5-FU infusion and systemic PEG-IFN-α2b combination therapy appears to be highly promising, although further prospective studies are required [42,44]. Reports of the use of HAIC with 5-FU combined with systemic IFN in advanced HCC are listed in Table 2.…”
Section: Chemotherapeutic Agentsmentioning
confidence: 99%
“…21 Each patient received an intra-arterial infusion of 5-FU (Kyowa Hakko Company, Tokyo, Japan) and subcutaneous PEG-IFNa-2b (PEG-Intron; MSD, Tokyo, Japan) or natural IFN-a (OIFs; Otsuka Pharmaceuticals Co., Tokyo, Japan); this combination therapy is henceforth referred to as 5-FU/IFN therapy. 6,9 One cycle of treatment lasted 4 weeks. 5-FU was administered into the hepatic artery over 5 h on days 1-5 of the first and second week of each 4-week cycle (500 mg/day).…”
Section: Treatment Protocolmentioning
confidence: 99%
“…Several studies have indicated the beneficial effect of a combination of intra-arterial 5-fluorouracil (5-FU) and systemic interferon-alpha (IFN-a) or pegylated interferon alpha-2b (PEG-IFNa-2b) for HCC with PVTT. [5][6][7][8][9] Recently, combination therapy that includes hepatic arterial infusion chemotherapy (HAIC) and three-dimensional conformal radiotherapy (3D-CRT) has been reported in patients with HCC and PVTT. 9 Advances in 3D-CRT have allowed more accurate delivery of higher radiation doses to the tumor, thus improving the antitumor effect and minimizing damage to normal tissue.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation